Formation of NaNbO3 crystals in dielectric glass and glass-ceramics of a Na2O-Nb2O5-AI 2O3-SiO2 system - S. Thongsaeng (2018)
Dielectric glass and glass-ceramics were derived from Na 2O-Nb2O5-Al2O3-SiO 2 system. Small amount of TiO2 were also introduced into glass compositions to study crystallization behavior of the glass with present of this nucleating agent. Conventional melt-quenching technique was employed for a glass production and the selected bulk glass samples were subjected to the heat-treatment process at appropriate temperature. After six different glass compositions were produced, and by observation with necked eyes, all obtained glass samples are in light brown color and some samples were opaque due to crystallization took place during quenching. Phase identification through XRD patterns show that there were 3 phases, NaNbO3, NaNbO8 and a sodium aluminum silicate compound, found in those opaque glass samples. NaNbO3 is a predominant phase in all samples. Fortunately, clear transparent glass was obtained from the composition with no TiO2 addition. Heat treatment of this glass did not induce phase change, three aforementioned phases still present. Increasing heat treatment time promoted a higher of observed intensity of NaNbO3. But the NaNbO3 crystalline size was not significantly developed with time. The dielectric response of the NaNbO3 crystals in the glass-ceramics samples are influenced by presence of other crystalline phases. © 2008 Trans Tech Publications, Switzerland.